Da'wah Messages in the Lyrics of the Song "Sandaran Hati" by Letto (Charles Sanders Peirce's Semiotic Analysis) - Hikmah, 1Isnaini Izzul; Chairiyah, Ummy (Proceedings of International Conference on Da'wa and Communication, 2023)
The problem studied in this study is the da’wa message in the lyrics of the songSandaran Hati by the band Letto, the aim of knowing the da’wa message contained in the lyricsof the song. This study uses a descriptive qualitative approach, with Charles Sanders Pierce'ssemiotic analysis technique, and uses the Da’wa Message theory by Moh. Ali Aziz. The resultsof this study found that the meaning contained in the lyrics of Letto's song "Sandaran Hati" isabout a servant who is losing his way and is in a downturn in his life but he still believes thatAllah is the place to ask for help and the best place to lean on. The manifestation of the sacredpromise that is bound between the servant and his Lord is to carry out His commands in the formof prayer. How a servant must be fully aware that prayer is only for a moment but must be donewholeheartedly (khusyuk) because it can give peace of mind both physically and mentally.Keywords: Da’wa Message, Song Lyrics, Charles Sanders Pierce's Semiotics.